Modelagem e desenvolvimento de formulários digitais acessíveis para pessoas surdas - Sales, Angelina Sthephanny da Silva (2020)
Even with access guaranteed by law, deaf people have difficulties accessing information. This limitation is evident when users who are deaf and not fluent in Portuguese (target users) have to inform their opinions as participants in forms, self-report scales or answer questionnaires. This is because the traditional data collection instruments used in these types of assessments are generally based on text, not on sign languages, which can impose access difficulties. The data collection modes present in the literature involving deaf people are not viable for scenarios in which the questionnaire author does not know Brazilian Sign Language (Libras) or, in the experiment, does not describe any appropriate tool for data collection. To minimize these problems, this work proposes a digital form model adapted to the communication needs and requirements of the deaf, including support for Libras, called LibrasForm. As a proof of concept, a solution was developed that allows the creation of accessible forms for deaf people, using the proposed model. The experiments contemplate the application of the solution in a questionnaire of general knowledge about Coronavirus and personal care applied to deaf users. The results showed that there is evidence that there is an improvement in the understanding of the content generated using LibrasForms. In addition, the solution has the potential to be used in other data collection scenarios and can be a functional and viable alternative to mitigate problems of access to information for deaf people, especially when human interpreters are not available.